The antimalarial resistome – finding new drug targets and their modes of action. (October 2020) - Carolino, Krypton; Winzeler, Elizabeth A
Highlights: In-vitro evolution and whole genome sequencing elucidates gene–drug interactions. Cellular thermal shift assay and mass spectrometry directly reveals small molecule compound–protein interactions. Metabolomic profiling complements target identification with broad mode of action. Abstract : To this day, malaria remains a global burden, affecting millions of people, especially those in sub-Saharan Africa and Asia. The rise of drug resistance to current antimalarial treatments, including artemisinin-based combination therapies, has made discovering new small molecule compounds with novel modes of action an urgent matter. The concerted effort to construct enormous compound libraries and develop high-throughput phenotypic screening assays to find compounds effective at specifically clearing malaria-causing Plasmodium parasites at any stage of the life cycle has provided many antimalarial prospects, but does not indicate their target or mode of action. Here, we review recent advances in antimalarial drug discovery efforts, focusing on the following 'omics' approaches in mode of action studies: IVIEWGA, CETSA, metabolomic profiling.